Planning for Groundwater Management for Future Smart Cities Vision in India: Exploring the Challenges and Opportunities (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Groundwater is best depicted as the world's genuine concealed fortune. Everywhere it has had any kind of effect in giving safe drinking water and employment security in all circumstances.Groundwater is the world's biggest open store of new water (barring ice sheets and icy masses) and constitutes around 94 of all new water. The volume of groundwater is right around 100 times that of surface water – around 10,530,000 km3. Groundwater is the most dependable wellspring of supply for consumable water and backings a wide cluster of financial and natural managements. Notwithstanding the long history of groundwater extraction all through human advancement, it has just been amid late decades that the utilization of groundwater has developed exponentially. Assessments of worldwide groundwater deliberation in the vicinity of 1950 and 2000 expanded to 1000 km3 of water in 2000 with in excess of 2 billion individuals relying upon groundwater for their day by day supply. Not just have populace increments and monetary development made a case for an ever bigger offer of groundwater, yet the nature of the asset are additionally progressively under strain. As utilization of the asset has expanded, so has its esteem and weakness, driving 'the concealed fortune' into the spotlight.